A multicentre, randomised controlled, non-inferiority trial, comparing high flow therapy with nasal continuous positive airway pressure as primary support for preterm infants with respiratory distress (the HIPSTER trial): study protocol. Issue 6 (24th June 2015) - Roberts, Calum T; Owen, Louise S; Manley, Brett J; Donath, Susan M; Davis, Peter G
Abstract : Introduction: High flow (HF) therapy is an increasingly popular mode of non-invasive respiratory support for preterm infants. While there is now evidence to support the use of HF to reduce extubation failure, there have been no appropriately designed and powered studies to assess the use of HF as primary respiratory support soon after birth. Our hypothesis is that HF is non-inferior to the standard treatment—nasal continuous positive airway pressure (NCPAP)— as primary respiratory support for preterm infants. Methods and analysis: The HIPSTER trial is an unblinded, international, multicentre, randomised, non-inferiority trial. Eligible infants are preterm infants of 28–36 +6 weeks' gestational age (GA) who require primary non-invasive respiratory support for respiratory distress in the first 24 h of life. Infants are randomised to treatment with either HF or NCPAP. The primary outcome is treatment failure within 72 h after randomisation, as determined by objective oxygenation, blood gas, and apnoea criteria, or the need for urgent intubation and mechanical ventilation. Secondary outcomes include the incidence of intubation, pneumothorax, bronchopulmonary dysplasia, nasal trauma, costs associated with hospital care and parental stress. With a specified non-inferiority margin of 10%, using a two-sided 95% CI and 90% power, the study requires 375 infants per group (total 750 infants). Ethics and dissemination: Ethical approval has been granted by the relevant human research ethics committees at The Royal Women's Hospital (13/12), The Royal Children's Hospital (33144A), The Mercy Hospital for Women (R13/34), and the South-Eastern Norway Regional Health Authority (2013/1657). The trial is currently recruiting at 9 centres in Australia and Norway. The trial results will be published in peer-reviewed international journals, and presented at national and international conferences. Trial registration number: Australian New Zealand Clinical Trials Registry ID: ACTRN12613000303741.